A Review on Phytochemical Screening and Pharmacological Activities of Ethno Botanical Plants from Family: Convolvulaceae - Meet Dhokiya; Riya Kadia; Nainesh Modi (International Journal of Scientific Research in Science and Technology, 2025)
The Convolvulaceae family is generally known as the “Morning Glory Family”. There are 20 genera and 158 species of the Convolvulaceae family reported in India; from them, 11 genera and 47 species are reported in Gujarat. Plants of this family are visible everywhere in Gujarat. Many kinds of plants from Convolvulaceae are used as medicine by our tribal people from ancient times. These types of plants are known as ethnobotanical plants. There are many plants like Ipomoea carnea (Jacq.), Ipomoea batatas (L.) Lam., Evolvulus nummularius (L.) L., Evolvulus alsinoides (L.), Merremia tridentata (L.) Hallier f., Argyreia speciosa (Linn F.) Sweet, and Argyreia cuneata (Willd.) Kar Gawl. that are commonly used as ethno medicine in our India. Three plant species were selected for a review focusing on their ethnomedicinal applications, phytochemical constituents, and pharmacological properties, named as I. carnea (Jacq.), A. speciosa (L. F.) Sweet and Merremia tridentata (L.) Hallier f. At the present time, the phytochemicals of the plants are mainly focused on the future and present medicinal uses due to their active potentials to treat many kinds of diseases. These plants are used for the different pharmacological activities like anti-bacterial, antioxidant, anti-diabetic, anti-inflammatory, and also as an ointment. Phytoconstituents like tannins, flavonoids, terpenoids, carbohydrates, alkaloids, polyphenols, etc. are present in it. I. carnea (Jacq.) leaves have potential to treat arthritis and skin diseases, and it contains phytoconstituents like neophytadiene and a high number of phenols. M. tridentata (L.) Hallier f. has the capacity to cure toothache, urinary infections, etc. it possesses several phytomolecules, like flavonoids such as diosmetin-7-o-diosmetin-7-o-β-glucosides, which is main active compound. A. speciosa (L. F.) leaves are used to treat gonorrhea, and chronic ulcer, that have epifriedelinol and quercetin as active constituents. These plants have capability to heal wounds. Many pharmacological tests of these plants are done for the anti-cancer, cardiovascular, anti-microbial, and many more activities.
Keywords: Convolvulaceae; Climbers; Ethnobotanical plant; Medicinal Plant; Phytochemicals; Pharmacological activities